2017
DOI: 10.3389/fphys.2017.00900
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neurogenesis through the Promotion of Energy Production Activity Is behind the Antidepressant-Like Effect of Colonial Green Alga, Botryococcus braunii

Abstract: Algae have been recognized as important resources providing functional components due to their capacity to exert beneficial effects on health. Therefore, there is increasing interest in investigating the biological activity of algae. In this study, we evaluated the antidepressant-like effect of the administration of 100 mg/kg/day of the ethanol extract of colonial green alga Botryococcus braunii (EEB) for 14 consecutive days in the forced swimming test (FST)-induced depression in imprinting control region (ICR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…The entire limbic area of the mouse brain containing the cortex, hippocampus, and amygdale was quickly dissected on ice and was minced for RNA extraction. Total RNA was purified from cerebral tissue using the ISOGEN kit (Nippon Gene Co. Ltd., Tokyo, Japan) following the manufacturer's instructions as reported previously . Total RNA was quantified and assessed for quality with NanoDrop 2000 spectrophotometer (Thermo SCIENTIFIC, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire limbic area of the mouse brain containing the cortex, hippocampus, and amygdale was quickly dissected on ice and was minced for RNA extraction. Total RNA was purified from cerebral tissue using the ISOGEN kit (Nippon Gene Co. Ltd., Tokyo, Japan) following the manufacturer's instructions as reported previously . Total RNA was quantified and assessed for quality with NanoDrop 2000 spectrophotometer (Thermo SCIENTIFIC, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%
“…DNA microarray analysis was performed as reported previously . Double‐stranded cDNA was synthesized from 100 ng of total RNA with the GeneAtlas 3′ IVT Express Kit (Affymetrix Inc., Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The dried algal powder was extracted following previous report [10]. Dry powder of Aurantiochytrium sp.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, microalgal biomass has also gained increasing interest as an attractive source for the sustainable production of physiologically active substances, such as polyunsaturated fatty acids (PUFAs), carotenoids, phycobiliproteins, polysaccharides, and phycotoxins. We have recently reported the antidepressant-like effects of the colonial green alga Botryococcus braunii by modulating neurogenesis and enhancing dopaminergic function [10].…”
Section: Introductionmentioning
confidence: 99%
“…A water-extracted fraction of Botryococcus braunii showed biological activities of dermatological interest [1]. Additionally, an ethanol extract of B. braunii showed antidepressant-like effects in a mouse behavior test [2]. Several studies have reported the anti-inflammatory effects of microalgal extracts on mammalian cells [35].…”
Section: Introductionmentioning
confidence: 99%